Pengaruh Kesadaran Dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Yang Dimoderasi Sosialisasi Perpajakan - Muhammad Rizki; Syaiful Syaiful (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The purpose of this study is to analyze and describe the role of tax socialization in moderating the influence of taxpayer awareness and understanding of taxes on individual taxpayer compliance (Case Study at Gresik Primary Tax Service Office). The population in this study were taxpayers registered at KPP Pratama Gresik, the research sample was taken by purposive sampling method with a research sample of 100 respondents. This research method uses quantitative methods. Data analysis is processed using Partial Least Squares (PLS) analysis with the help of Smart-Pls 3.0 software. The results of this study indicate that taxpayer awareness, understanding of taxation, and taxation socialization affect the compliance of individual taxpayers. While taxation socialization cannot moderate the relationship between taxpayer awareness and understanding of taxation on individual taxpayer compliance.